Hegel’s Critique of Indian Philosophy (Revista Eletrônica Estudos Hegelianos, 2023)
In his Lessons on the History of Philosophy, Hegel presented a negative view on the contributions of China and India. In particular, he stated that the Indian thought could not be classified as philosophical. Hegel’s assessment has been influential in the attitude of philosophy departments, in denying the inclusion of the philosophy of India in their syllabi. This paper presents a detailed analysis of Hegel’s criticism of Indian thought, taking into account the European knowledge about India in the early nineteenth century. The conclusion is that Hegel’s criticism was not well-founded.